Structures Congress 2014 2014
DOI: 10.1061/9780784413357.117
|View full text |Cite
|
Sign up to set email alerts
|

Damage Reconnaissance and Seismic Response Prediction of an East Coast U.S. Building Subjected to 2011 Virginia Earthquake

Abstract: During the 2011 Mineral, Virginia Earthquake the Smithsonian Institute Museum Support Center (MSC) sustained considerable structural damage. An in-depth study was conducted to investigate the behavior of MSC during this earthquake and its potential implication on seismic risk of East Coast U.S. structures. The damage sustained by this building is documented and it is observed that the severity of damage is not uniformly distributed in the floor plan. A finite element model is created to perform the seismic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…As a result, there is one suite of ground motions for the Design Basis Earthquake (DBE) hazard level and another for the Maximum Considered Earthquake (MCE) hazard level. The soil profile (seeFigure 8) is the same as the one used inChu et al (2014) that results in a calculated response consistent with the observed damage. The USGS Uniform Hazard Response Spectra (UHRS) (Petersen et al 2008) for the DBE and MCE hazard levels, which correspond to a return period of 475 years and 2475 years, respectively, at the site of the MSC are employed as the target spectra in selecting the bedrock motions.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…As a result, there is one suite of ground motions for the Design Basis Earthquake (DBE) hazard level and another for the Maximum Considered Earthquake (MCE) hazard level. The soil profile (seeFigure 8) is the same as the one used inChu et al (2014) that results in a calculated response consistent with the observed damage. The USGS Uniform Hazard Response Spectra (UHRS) (Petersen et al 2008) for the DBE and MCE hazard levels, which correspond to a return period of 475 years and 2475 years, respectively, at the site of the MSC are employed as the target spectra in selecting the bedrock motions.…”
mentioning
confidence: 83%
“…The 700,000 square feet zigzag-shaped complex is divided into three parts: the five "Pods"; five Offices; and an interconnecting corridor called the "Street" (Figure 1b). More information about the concrete structure can be found in Chu et al (2014). More information about the concrete structure can be found in Chu et al (2014).…”
Section: Building Descriptionmentioning
confidence: 99%
See 3 more Smart Citations